Towards a sustainable systems framework: the assessment of Silvoarable Agroforestry as an innovative cropping practice - Park, Julian (Cranfield University, 1993)
Questions are continually being asked about the direction in which land based production in the UK is evolving. Present systems are criticised as being damaging to the wider environment and rural communities. Of equal concern is the reliance upon non-renewable resources within agricultural systems and the effect "modern farming" is having on agroecosystem processes. This thesis uses an integrative research approach to investigate the sustainability of land based production. It is argued that the view of what constitutes a sustainable system is constantly changing suggesting that increasingly sustainable systems are those which evolve along pathways which keep future options open. It is recognised that to do this links have to be made between the concept of sustainability in physical and social systems and the policy and decision makers who play a major part in the change process. A series of interfaces are explored using a variety of research activities which demonstrate one approach for linking the concept of sustainability to the provision of policy relevant information. Silvoarable agroforestry is used as a research medium or case study which enables the application of the research approach to an innovative cropping practice which could possibly increase the degree of sustainability of land based production. The contribution of the thesis is interpreted at three levels. 1. The application of a integrative research approach to synthesis information from both physical and social systems in a manner which enables the concept of sustainability to be linked to human managed production systems which interact with the natural environment, 2. The use and linking of several research activities, some of which provide a contribution to methods of working within individual disciplines, to provide a methodology for the assessment of the potential of innovative cropping practices, 3. The assessment of silvoarable agroforestry as an innovative cropping practice. Information is provided on the effects of these systems on agroecosystem processes, the economic and financial implications of their uptake, the technical issues as perceived by the farmers and finally the likelihood of uptake of these systems.